Radiation Oncology - Ahmad, Usama; Aftab Siddiqui, Mohd; Akhtar, Juber (IntechOpen, 2022)
Radiation Oncology provides a comprehensive overview of radiotherapy for cancer treatment. It discusses brachytherapy, external radiation, and photodynamic therapy for different types of cancers, as well as dosimetry audits, which ensure that the accurate therapeutic dose is delivered to patients undergoing radiotherapy. The need of the hour for radiotherapy procedures that provide maximum clinical care with safety and efficacy and also enhance the advantage of treatment and diminish the risks of late complications.